Investigation of injectable drug utilization in primary care: A focus on different age groups in pediatric population - AKICI, AHMET (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2020)
Objective: The suitability of the injectables may vary across different age groups especially for children; therefore, knowledge on their usage patterns is critical in terms of rational pharmacotherapy. This study aimed to investigate pediatric injectable drug utilization in primary care with a focus on different age groups. Method: By simple sampling method, 100 prescriptions that contained at least one injectable drug were randomly selected for each month of the year in 32 provinces of Turkey (n = 38 .400). Among these prescriptions, injectable drugs that were for children (< 18 years) were analyzed. Patterns of injectable drug utilization were compared according to the pediatric age group of infants, children, and adolescents. Results: We identified 5446 patients (14.2%) with a mean age of 7.4 +/- 5.2 years and a slight male tendency in distribution (53.8%). The most common indication for these patients was for the respiratory system (65.4%), of which 96.3% were respiratory tract infections. While less pronounced in adolescents than in infants and children, the most commonly prescribed injectable drugs were antibiotics in all age groups (61.5% vs. 78.6% and 79.9%, P < 0.0001), which was upheld across all seasons. More than 90% of all prescribed injectable antibiotics consisted of penicillins and cephalosporins; the latter being predominant in infants (67.4%) compared with penicillins in children (53.9%) and adolescents (59.0%). Analgesics and insulin were found to be prescribed more frequently to adolescents than they were to infants and children (P < 0.0001 and P < 0.0001, respectively). The mean cost of prescription and injectable drugs per encounter was significantly more likely to escalate with increasing age (P < 0.0001 and P < 0.0001, respectively). Conclusion: Considering the predominance of antibiotics as well as the substantially higher prescription of third-generation cephalosporins in primary care, which was especially more marked for younger children, our study indicates an inappropriate use of injectable drugs by primary care physicians for managing medical conditions in the pediatric population. (C) 2020 French Society of Pediatrics. Published by Elsevier Masson SAS. All rights reserved.
Keywords: Pediatrics; Antibiotics; Injectable; Primary care; Prescribing; ASSOCIATION; PREVENTION; MANAGEMENT; DIAGNOSIS; DISEASES; CHILDREN